Chapter Piccola guida per sviluppare strumenti terminologici - Kranebitter, Klara (Proceedings e report, 2021)
Developing terminology products as tools for organizing and transferring specialized knowledge requires careful considerations already during the planning stage. The main content of this paper is a checklist, which is the result of reflections gathered during the reprogramming and restyling of the Information System for Legal Terminology bistro (http://bistro.eurac.edu). bistro is an application used to publish the data contained in a multilingual terminological data base. The checklist is designed as a starting point and reference for the conception and structuring of terminology tools, e. g. online terminology reference tools. Its aim is to help identify needs and, at the same time, to guide developers in the basic choices to be made already in the planning stage.